Solved problems in dynamical systems and control - Machado, J. A. Tenreiro; Lopes, António M.; Valério, Duarte; Galhano, Alexandra M. (The Institution of Engineering and Technology, 2016)
This book presents a collection of exercises on dynamical systems, modelling and control. Each topic covered includes a summary of the theoretical background, problems with solutions, and further exercises. Topics covered include: block diagram algebra and system transfer functions; mathematical models; analysis of continuous systems in the time domain; root locus analysis; frequency domain analysis; PID controller synthesis; state space analysis of continuous systems; controller synthesis by pole placement; discrete time systems and the z transform; analysis of non-linear systems with the describing function method; analysis of nonlinear systems with the phase plane method; and fractional order systems and controllers. Based on tried-and-tested problems and solutions that the authors use in teaching over 500 students each year, this book is essential reading for advanced students with courses in modelling and control in engineering, applied mathematics, biomathematics and physics.
Keywords: Differentiable dynamical systems.; Dynamics.; Differential equations.; elektronické knihy; electronic books